Strateg Strategi community marketing dalam membangun brand loyalty somthinc di tik tok shop - fajar ritonga (JEKBI: Jurnal Ekonomi dan Bisnis Islam, 2024)
The development of digital marketing has contributed to strengthening the business ecosystem. Digital marketing not only transforms traditional offline marketing into online marketing but also reshapes the marketing ecosystem itself. Communities that once gathered in physical spaces now connect virtually through digital marketing. One of the products that implements community marketing is Somethinc. This study aims to analyze the community marketing strategy in building brand loyalty for Somethinc on TikTok Shop. The research employs a descriptive qualitative approach. Data was collected through digital exploration and observation, supported by secondary data from official publications and literature relevant to the research topic. The findings indicate that Somethinc’s community marketing strategy on TikTok Shop has contributed to building brand loyalty. By leveraging interactive features such as live streaming, user-generated content (UGC), and collaborations with influencers, Somethinc has successfully created an engaged and active customer community. This success is reflected in the high number of followers, increased interactions, and sales data showing continuous positive growth. Community-based marketing strategies allow Somethinc to establish stronger emotional connections with consumers. Direct interactions with customers through TikTok not only enhance engagement but also encourage repeat purchases and recommendations from loyal customers. Additionally, Somethinc’s success is supported by the effective utilization of marketing trends, including the integration of marketing content with social commerce methods, enabling customers to engage in a more interactive and personalized shopping experience. This study suggests that Somethinc should continue product innovation to maintain business sustainability.